IMPROVING LOW CLASS WRITING SKILLS AT UPT SDN 1 GANDANGBATU SILLANAN - Esther Ropinis; Sundari Hamid (Teaching English as a Foreign Language Overseas Journal, 2023)
This study aims to determine the improvement of lower grade writing skills through media images in class II UPT SDN 1 Gandangbatu Sillanan students for the 2020/2021 academic year. The subjects of this study were class II students with a total of 27 students consisting of 14 male students and 13 female students. The method used is a class action research method (Classroom Action Research) where the analysis of learning outcomes is reflected in the next lesson. This research was divided into two cycles, namely cycle I and cycle II. Based on the research results, the writing ability of the low grade students in grade II can be improved by using media images. This can be proven from the increase in low class writing skills. In the pre-cycle the average value obtained was 55.37, it experienced an increase in the first cycle the average value obtained was 66.67, and experienced an increase in the second cycle the average value became 78.89. The conclusion of this study shows that media images can improve writing skills in class II students in class II.